2020
DOI: 10.1021/jacs.9b13019
|View full text |Cite
|
Sign up to set email alerts
|

Axially Chiral Spiro-Conjugated Carbon-Bridged p-Phenylenevinylene Congeners: Synthetic Design and Materials Properties

Abstract: Spiro-conjugated systems are attracting considerable interest for their chiroptical properties and because of their compact structure the small reorganization energy upon electronic excitation or ionization. We report here a modular and convergent synthesis of axially chiral spiro-conjugated carbon-bridged p-phenylenevinylenes (spiro-CPVs) in a racemic and optically active form where two carbon-bridged p-phenylenevinylene molecules are connected by a spiro carbon atom. Our synthetic design focuses on the C 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 84 publications
1
45
0
1
Order By: Relevance
“…The UV-vis absorption spectrum of compound 31 is highly comparable to compound 1, as reported by Poriel and Rault-Berthelot et al [14] However, compound 31 possessed reduced structural rigidity and a larger Stokes shift (15 nm), compared with compound 1 and its equivalents 16-20. Recently, Nakamura et al reported the axially chiral spiro-conjugated carbon-bridged p-phenylenevinylene compound 32, [35] (Scheme 12) which exhibited a PLQY of 74 % and a decomposition temperature of 335°C (with 5 % weight loss). More importantly, a series of compound 32 derivatives with four diarylamine units were efficiently obtained with a higher than 60 % yield, which presented a low hole mobility of 3.84 × 10 À 5 cm 2 V À 1 s À 1 ; highly comparable with the most widely used hole-transporting material: 2,2',7,7'-tetrakis (N,N-bis(p-methoxy-phenyl)amino)-9,9'-spirobifluorene (spiro-OMeTAD).…”
Section: Other Extensions Of Condensed Spirobifluorenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV-vis absorption spectrum of compound 31 is highly comparable to compound 1, as reported by Poriel and Rault-Berthelot et al [14] However, compound 31 possessed reduced structural rigidity and a larger Stokes shift (15 nm), compared with compound 1 and its equivalents 16-20. Recently, Nakamura et al reported the axially chiral spiro-conjugated carbon-bridged p-phenylenevinylene compound 32, [35] (Scheme 12) which exhibited a PLQY of 74 % and a decomposition temperature of 335°C (with 5 % weight loss). More importantly, a series of compound 32 derivatives with four diarylamine units were efficiently obtained with a higher than 60 % yield, which presented a low hole mobility of 3.84 × 10 À 5 cm 2 V À 1 s À 1 ; highly comparable with the most widely used hole-transporting material: 2,2',7,7'-tetrakis (N,N-bis(p-methoxy-phenyl)amino)-9,9'-spirobifluorene (spiro-OMeTAD).…”
Section: Other Extensions Of Condensed Spirobifluorenesmentioning
confidence: 99%
“…More importantly, a series of compound 32 derivatives with four diarylamine units were efficiently obtained with a higher than 60 % yield, which presented a low hole mobility of 3.84 × 10 À 5 cm 2 V À 1 s À 1 ; highly comparable with the most widely used hole-transporting material: 2,2',7,7'-tetrakis (N,N-bis(p-methoxy-phenyl)amino)-9,9'-spirobifluorene (spiro-OMeTAD). [35] Trispirocyclic hydrocarbon compound 33 (Scheme 13), possessing three 9-fluorene moieties around the core of truxene, was synthesized via truxenone with 2-bromobiphenyl coupling. [36] Compound 33 is a colorless solid, sparingly soluble in common organic solvents, and has a melting point of 500°C.…”
Section: Other Extensions Of Condensed Spirobifluorenesmentioning
confidence: 99%
“…[1f] Spirocyclic compounds have also found some interesting applications as privileged ligands for asymmetric catalysis such as spinol, [2] or in the production of circularly polarized photoluminescence. [3] Furthermore, the spirocyclic motif is becoming a prevalent template in drug discovery, [4] since this structural feature conveys both increased three-dimensionality for potential improved activity, and novelty for patenting purposes. An example of spirocyclic drugs is the marketed fenspiride, [5] used for the treatment of some respiratory diseases (Figure 1).…”
mentioning
confidence: 99%
“…Thus, simple 2D aromatics can be elaborated to 3D structures in precise platforms. Spirocycles are an important class of 3D framework and have found widespread applications in material sciences owing to their outstanding photophysical and optical properties, especially for naphthol‐derived spirocycles . C−H activation has enabled the facile construction of diverse spirocycles .…”
Section: Methodsmentioning
confidence: 99%
“…Spirocycles are an important class of 3D framework and have found widespread applications in material sciences owing to their outstanding photophysical and optical properties, especially for naphthol‐derived spirocycles . C−H activation has enabled the facile construction of diverse spirocycles . In particular, CpRh III complexes stand out as prominent catalysts in spiroannulations of arenes with unsaturated coupling reagents such as alkynes, alkenes, and diazo reagents .…”
Section: Methodsmentioning
confidence: 99%